Simple Solution‐Processed Approach for Nanoscale Coverage of Perovskite on Textured Silicon Surface Enabling Highly Efficient Perovskite/Si Tandem Solar Cells. Issue 1 (27th November 2020) - Wang, Jiayuan; Gao, Chao; Wang, Xin; Wang, Yangrunqian; Cheng, Zhendong; Liu, Hong; Shen, Wenzhong
Abstract : Existing methods toward the preparation of perovskite deposited on textured silicon surfaces are technically complicated for perovskite/Si monolithic tandem solar cells (TSCs). Herein, a handy solvent engineering approach of introducing starch additive in MAPbI3 ‐based one‐step spin coating at room temperature is reported. The effect of different starch contents in perovskite precursor solution on morphological, structural, optical, and photovoltaic properties of the perovskite films is investigated. The starch enhances the solution viscosity and establishes hydrogen bonds with CH3 NH3 +, leading to the formation of almost same perovskite crystal structure films suitable for textured silicon surfaces. The perovskite film with a starch concentration of 5 wt% realizes full coverage on the textured silicon surface with an average thickness around 600 nm. Both the perovskite film and corresponding plane solar cell exhibit stable crystal structure and device performance due to the starch molecules located at the perovskite grain boundaries to lock the water molecules. The potential of pairing the yielded quasiconformal nanoscale coverage of perovskite layers with textured silicon surfaces is evaluated, and the uniform light absorption in perovskite layers and good match of the current density in perovskite/Si monolithic TSCs, with the best‐calculated cell efficiency exceeding 29%, are demonstrated. Abstract : A starch‐modified solution‐processed approach is reported to realize full coverage of nanoscale perovskite on textured silicon surfaces. The starch enhances the viscosity of the perovskite precursor solution, and establishes the hydrogen bonds with the CH3 NH3 + cation. The yielded quasi‐conformal nanoscale coverage exhibits good match of current density in perovskite/Si monolithic tandem solar cells, with the best‐calculated cell efficiency over 29%.